Intraoperative evaluation of the intestinal wall viability - Nikita A. Adamenkov; Andrian V. Mamoshin; Viktor V. Dremin; Elena V. Potapova; Valery V. Shupletsov; Yuri V. Ivanov; Dmitry N. Panchenkov; Andrey V. Dunaev (Клиническая практика)
An analysis of data from national and foreign literature was carried out in terms of intraoperative determination of the intestinal viability in cases of developing the diseases in the abdominal cavity organs, associated with impaired intestinal blood supply. The basis of this work is the analysis of the modern literature on the methods of intraoperative evaluation of mesenteric ischemia. Impaired mesenteric blood supply is often the consequence of a number of reasons of developing critical conditions (mesenteric thrombosis, acute adhesive intestinal obstruction, incarcerated hernia etc.), also representing a high risk factor for lethal outcomes. Special attention is paid to the occlusion-related pathogenetic mechanism of developing mesenteric ischemia, which is accompanied by rapid development of irreversible morphological changes in the tissues and by significant disorders in the homeostasis systems of the organism. The generally available method for visual evaluation of the intestine viability is not always valid in terms of determining the degree of intensity of the ischemic changes in the intestinal wall. The algorithm of determining the intestine viability includes the determination of the intestine color, the peristaltic motions, the pulsation and the blood filling of mesenteric vessels with dynamic evaluation of these signs after the injecting the local anesthetic drug solution into the mesenterium and after “warming” the intestine with towels soaked in warm sodium chloride solution. In the current surgical conditions, a more precise method is required for intraoperative determination of the tissue viability. For the purpose of the objective evaluation of the intestinal blood supply, the recommendations include using intraoperative ultrasonic and laser Doppler flowmetry, as well as the regional transillumination angiotensometry of the intramural vessels in the small intestine. At the same time, a number of optical spectroscopy and visualization methods show high sensitivity to changes in blood microcirculation without using exogenous contrasting, which can also be successfully used when evaluating the intestinal circulation. According to data from modern literature, there is still controversy on the efficiency of various methods for intraoperative evaluation of disorders of the regional blood microcirculation and the intestine viability, which justifies the conduct of further research works.